[44Sc]Sc-PSMA-617 Biodistribution and Dosimetry in Patients With Metastatic Castration-Resistant Prostate Carcinoma. (May 2018) - Khawar, Ambreen; Eppard, Elisabeth; Sinnes, Jean Phlippe; Roesch, Frank; Ahmadzadehfar, Hojjat; Kürpig, Stefan; Meisenheimer, Michael; Gaertner, Florian C.; Essler, Markus; Bundschuh, Ralph A.
Abstract : Aim: [ 44 Sc]Sc-PSMA-617 with 3.9-hour half-life, in vitro and in vivo characteristics similar to [ 177 Lu]Lu-PSMA-617 and possibility of delayed imaging after 24 hours or later, implies it to be advantageous than [ 68 Ga]Ga-PSMA-617 for pretherapeutic dosimetric assessment for [ 177 Lu]Lu-PSMA-617 in metastatic castration-resistant prostate carcinoma (mCRPC) patients. In this study, we investigated biodistribution and radiation exposure to normal organs with [ 44 Sc]Sc-PSMA-617 in mCRPC patients. Methods: Five mCRPC patients (mean age, 69 years) enrolled for [ 177 Lu]Lu-PSMA-617 therapy were injected with 40–62 MBq [ 44 Sc]Sc-PSMA-617 intravenously; Siemens Biograph 2 PET/CT system was used to acquire dynamic PET data (30 minutes) in list mode over the abdomen, followed by the collection of static PET/CT images (skull to mid-thigh) at 45 minutes, 2 and approximately 20 hours postinjection. Time-dependent changes in percentage activity in source organs (kidneys, bladder, salivary glands, small intestine, liver, spleen, and whole body) were determined. Bone marrow and urinary bladder contents residence time were also calculated. Source organs residence time, organ-absorbed doses, and effective doses were determined using OLINDA/EXM software. Results: Physiological tracer uptake was seen in kidneys, liver, spleen, small intestine, urinary bladder, and salivary glands and in metastases. Kidneys with highest radiation absorbed dose of 3.19E-01 mSv/MBq were the critical organs, followed by urinary bladder wall (2.24E-01 mSv/MBq, spleen [1.85E-01], salivary glands [1.11E-01], and liver [1.07E-01] mSv/MBq). Red marrow dose was found to be 3.31E-02 mSv/MBq. The mean effective dose of 3.89E-02 mSv/MBq and effective dose of 1.95 mSv was estimated from 50 MBq (treatment planning dose) of [ 44 Sc]Sc-PSMA-617. Conclusions: [ 44 Sc]Sc-PSMA-617 is found to be a very promising radiopharmaceutical that can be used for pre [ 177 Lu]Lu-PSMA-617 therapeutic dosimetric assessment.